Microwave assisted processing of X8R nanocrystalline BaTiO3 based ceramic capacitors and multilayer devices - S. Sumithra; K. Annapoorani; A. Ellmore; B. Vaidhyanathan (Open Ceramics, 2022)
BaTiO3 based multilayer ceramic capacitor (MLCC) is an important component in electronic devices. Achieving high dielectric performance, miniaturisation and cost effectiveness are still challenging. Co-sintering ceramic layers with metal electrodes and use of expensive Pt and high-Pd content compositions as electrodes are other key issues. Thus, the major factors that could lead to cost effectiveness of MLCCs are reduction in sintering temperature and using less expensive metal electrodes without compromising dielectric performance and these traits could auger well for the next generation low-cost high performance electroceramic devices – this is the subject matter of the present study.In this work, initially we have fabricated and analysed the dielectric performance of BaTiO3 (BT) ceramics with different BT particle sizes (50 nm, 100 nm and 200 nm). Based on results, 200 nm BaTiO3 was used for further studies due to its superior dielectric performance. Then, to reduce the sintering temperature and improve the dielectric performance of 200 nm BaTiO3 ceramics, Bi2O3 was used as a dopant which acts both as a sintering aid and helps to improve the dielectric performance. A combination of rare earth dopant system (proprietary from the industrial partner Knowles, UK) with Bi2O3 was also added to tune the defect chemistry of BaTiO3 for enhancement in dielectric performance further. A homogeneously mixed BT-based ceramic slurry system (containing the above dopants) with optimum rheology was developed using a non-aqueous medium, dispersant and a binder system. Addition of glass frits for lowering the sintering temperature and its effect on dielectric performance was also investigated on both discs (made using dry pressing of the powders obtained via drying of the slurry) as well as multilayer ceramic capacitors (MLCCs) fabricated through screen printing. Conventional, microwave and hybrid sintering procedures were employed for the densification of the electroceramic devices and these were characterized for density, microstructure, composition and dielectric performance systematically. Conventional sintering resulted in undesired large micron sized surface features which are detrimental to device durability, whereas formation and growth of these features have been demonstrated to be significantly minimised using the rapid microwave assisted sintering procedures for the first time. Further efficient co-sintering of ceramic layers with less expensive (Ag/Pd) alloy has also been accomplished using the microwave methodology. The resultant BaTiO3 based capacitive devices exhibited high dielectric permittivity, superior X8R performance and low dissipation factor, asserting their massive potential for widespread high temperature applications in automotive, sensing and space sectors.